Monitoring and control of labor protection instructions - Mezentseva, I. O.; Vambol, S. O.; Mezentsev, S. M.; Sokol, O. V. (Державний біотехнологічний університет, 2024)
The study shows the number of accidents for the period 2017-2022. The dynamics of the causes of industrial injuries for the specified period are given. Considerations are presented regarding the organizational reasons behind the greatest number of accidents. It is noted that it is necessary to improve the process of reviewing, updating and developing instructions on labor protection.
Keywords: monitoring; labor protection instructions; accidents; ndustrial injuries